Energía y asentamientos humanos en el Caribe del Este: desafíos y oportunidades - Rojas, Eduardo (Revista EURE - Revista de Estudios Urbano Regionales, 1982)
Based on a review of the energy situation in the countries of the Eastern Caribbean, Antigua, Dominica, Saint Lucía, Saint Vincent and Granada and in particular as it relates to the rural population and the urban poor, the author argues in favor of incorporating a spatial dimension to energy development planning and implementation. It is suggested that energy planning at the human settlement level is capable of incorporating the essentially local aspects of non conventional energy development, a pre-requisite for achieving a more self-reliant energy situation in the Eastern Caribbean. Facts and figures concerning the increasingly large burden that energy imports is representing for the development of these countries are reviewed side by side with data concerning non conventional energy development opportunities and problemes. They constitute the background against which the author substanciate his proposals.